2022
DOI: 10.1186/s12957-022-02730-y
|View full text |Cite
|
Sign up to set email alerts
|

Total laparoscopic pancreaticoduodenectomy with left posterior superior mesenteric artery first-approach and plexus-preserving circumferential lymphadenectomy: step-by-step technique with a surgical case report (with video)

Abstract: Introduction Total laparoscopic pancreaticoduodenectomy (tLPD) for cancer of the Vater remains a challenging procedure. Recently, several meta-analyses showed the superior aspects of “superior mesenteric artery (SMA)-first approach,” “systematic mesopancreas dissection,” and “circumferential lymphadenectomy around SMA” in increasing R0 resection rate and reducing postoperative complications including pancreatic fistula and bleeding as well as improving overall survival particularly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Six articles examined the left SMA-first approach in LPD ( Fig. 7 a,b) [ 8 , 9 , [34] , [35] , [36] , [37] ]. Shen et al [ 35 ] demonstrated the reformation and improvement of a modified no-touch isolation technique emphasizing exploration of the distal section of the SMV and the SMA's left side prior to determining resectability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six articles examined the left SMA-first approach in LPD ( Fig. 7 a,b) [ 8 , 9 , [34] , [35] , [36] , [37] ]. Shen et al [ 35 ] demonstrated the reformation and improvement of a modified no-touch isolation technique emphasizing exploration of the distal section of the SMV and the SMA's left side prior to determining resectability.…”
Section: Resultsmentioning
confidence: 99%
“…This reduces the likelihood of tumor cell metastasis by ensuring that all procedures adhere to oncologic no-touch rules. Khiem et al [ 36 ] revealed a successful LPD via the left posterior approach involving SMA plexus preservation, while Cho et al [ 34 ] reported on this approach in detail. Liao et al [ 37 ] described a detailed surgical strategy to determine resectability by first preferentially exposing the SMA's left side, which also ensures the surgical effect and shortens the operative time, particularly for the resected segment.…”
Section: Resultsmentioning
confidence: 99%
“…The artery-first approach was first proposed by Pessaux [ 22 ] and has since been widely used in OPD, where its advantages have been recognized [ 8 ]. Laparoscopy has a flexible viewing angle from the caudal to the cephalic side as well as a unique dorsal perspective which facilitates the anatomy and exposure of the SMA, thus the SMA-first approach has also begun to be used in LPD [ 9 12 , 23 , 24 ]. The advantages of the LPD artery-first approach are as follows.…”
Section: Discussionmentioning
confidence: 99%
“…In the laparotomic approach, an upper abdominal incision was performed to explore the peritoneum to exclude metastases. Meanwhile, in the laparoscopic approach, we use 5 trocars, which procedure was described in our technical article [ 21 ]. We use three approaches to first explore the SMA root:…”
Section: Methodsmentioning
confidence: 99%